ANALISIS DIMENSI METRIK DENGAN HIMPUNAN PEMBEDA TERHUBUNG PADA GRAF KHUSUS KELUARGA POHON DIKAITKAN KETERAMPILAN BERPIKIR TINGKAT TINGGI - Sulistio, Wahyu; Slamin, Slamin; dafik, dafik (Department of Mathematics Education , University of Jember, 2015)
Abstract. Metrice dimension with connected resolving set is a minimal cardinality from resolving set on graph G that make metrice representation from every point v on graph G to the resolving set W different each other and every point of resolving set must be connected each other. For example G is a connected graph and W = w1,w2,...,wk are element of V. for every v∈V, position vectorr (v|W)=(d(v,w1),d(v,w2),...,d(v,wk)) are called metrice representation from v to W. Whenevery different point on V has different metrice representation, so W is called resolving set of G. Minimum cardinality from a resolving set of G for the next is call Metrice dimension of G that has been notation with dim(G). Resolving set of W is said connected if induction subgraph of <W> doesn't have a separated point. Minimum cardinality of connected resolving set from G is called connected resolving set of G that been notation with nr(G). In this research develop Metrice dimension with connected resolving set on special graph of tree specially on star graph, E graph, reguler catepillar graph, reguler banana tree grap hand reguler fireworkgraph. The result from this research is a theorem that indicated minimum cardinality of connected resolving set ornr(G) and how the link between metrice dimension with High Order Thinking Skill (HOTS). Keywords: Metrice Dimension, Connected resolving set, value of connected resolving set, HOTS